Atmospheric pressure plasma for surface modification - Wolf, Rory A. (Hoboken, N.J. : John Wiley & Sons, 2013)
"This Book's focus and intent is to impart an understanding of the practical application of atmospheric plasma for the advancement of a wide range of current and emerging technologies. The primary key feature of this book is the introduction of over thirteen years of practical experimental evidence of successful surface modifications by atmospheric plasma methods. It offers a handbook-based approach for leveraging and optimizing atmospheric plasma technologies which are currently in commercial use. It also offers a complete treatment of both basic plasma physics and industrial plasma processing with the intention of becoming a primary reference for students and professionals. The reader will learn the mechanisms which control and operate atmospheric plasma technologies and how these technologies can be leveraged to develop in-line continuous processing of a wide variety of substrates. Readers will gain an understanding of specific surface modification effects by atmospheric plasmas, and how to best characterize those modifications to optimize surface cleaning and functionalization for adhesion promotion. The book also features a series of chapters written to address practical surface modification effects of atmospheric plasmas within specific application markets, and a commercially-focused assessment of those effects"--
Machine generated contents note: Preface xi 1. Plasma -- The Fourth State of Matter 1 1.1 Fundamentals of Plasmas 1 1.2 Thermal vs. Nonthermal Plasmas 6 1.3 Mechanisms for Surfaces Reactions 22 2. Plasmas for Surface Modification 27 2.1 Low-Pressure Plasmas 28 2.2 Microwave Systems 31 2.3 Physical Vapor Deposition Systems 33 2.4 Atmospheric Plasma Systems 42 2.5 Atmospheric Plasma Precursor Deposition Systems 51 3. Atmospheric Plasma Surface Modification Effects 55 3.1 Surface Cleaning 56 3.2 Surface Etching 63 3.3 Surface Functionalization 66 3.4 Grafting and Surface Polymerization Effects 75 4. Characterization Methods of Atmospheric Plasma Surface Modifications 81 4.1 Surface Characterization Techniques 81 4.2 X-Ray Photoelectron Spectroscopy (XPS) 82 4.3 Static Secondary Ion Mass Spectrometry by Time-of-Flight (TOF-SIMS) 86 4.4 Atomic Force Microscopy 89 4.5 Scanning Electron Microscopy (TEM) 97 4.7 Visual Methodologies 98 5. Atmospheric Plasma Modification of Roll-to-Roll Polymeric Surfaces 109 5.1 Material Classifications and Applications 110 5.2 Atmospheric Plasma Processing Surface Effects 116 5.3 Assessments of Surface Modification Effects 117 6. Atmospheric Plasma Modification of Three-Dimensional Polymeric Surfaces 121 6.1 Material Classifications and Applications 125 6.2 Atmospheric Plasma Processing Surface Effects 129 6.3 Assessments of Surface Modification Effects 135 7. Atmospheric Plasma Modification of Textile Surfaces 139 7.1 Material Classifications and Applications 141 7.2 Atmospheric Plasma Processing Surface Effects 145 7.3 Assessments of Surface Modification Effects 151 8. Atmospheric Plasma Modification of Paper Surfaces 155 8.1 Material Classifications and Applications 157 8.2 Atmospheric Plasma Processing Surface Effects 162 8.3 Assessments of Surface Modification Effects 164 9. Atmospheric Plasma Modification of Metal Surfaces 167 9.1 Material Classifications and Applications 168 9.2 Atmospheric Plasma Processing Surface Effects 173 9.3 Assessments of Surface Modification Effects 177 10. Atmospheric Plasma Surface Antimicrobial Effects 181 10.1 Antimicrobial Surface Effects 183 10.2 Inactivation and Sterilization Methods -- Medical 187 10.3 Inactivation and Sterilization Methods -- Food 189 11. Economic and Ecological Considerations 195 11.1 Operating Cost Comparison of Atmospheric Plasma Systems 196 11.2 Environmental/Sustainable Advantages 201 12. Emerging and Future Atmospheric Plasma Applications 205 12.1 Solar and Other Alternative Energy Systems 205 12.2 Energy Storage Technologies 211 12.3 Aviation and Aerospace Applications 215 12.4 Electronic Device Fabrication 216 12.5 Air Purification Applications 220 12.6 Medical Engineering 221 13. Economic and Environmental Assessment 225 13.1 Goal and Scope 226 13.2 Functional Units 227 13.3 System Boundaries 230 13.4 Data Documentation 232 13.5 Lifecycle Interpretation 233.
Includes bibliographical references and index.
Keywords: Low temperature plasmas -- Industrial applications; Surfaces (Technology); TECHNOLOGY & ENGINEERING -- Industrial Engineering; TECHNOLOGY & ENGINEERING -- Mechanical; Nonequilibrium plasmas; Electronic books